Methodological issues in assessing job stress and burnout in psychosocial research: Methodological issues in assessing job stress and burnout - Campanini, Paolo (La Medicina del Lavoro, 2021)
In recent years, researchers identified a “reproducibility crisis” of scientific studies. In assessing job stress and burnout in psychosocial research two biases that prevent the results from being generalized are common: sample bias (included web survey) and common method bias using questionnaires. These issues are commented and remedies are proposed to prevent or contain biases.